2023
DOI: 10.3390/diagnostics13020259
|View full text |Cite
|
Sign up to set email alerts
|

Soluble ST2 as a Useful Biomarker for Predicting Clinical Outcomes in Hospitalized COVID-19 Patients

Abstract: Soluble suppression of tumorigenesis-2 (sST2) is an emerging biomarker for sepsis as well as for heart failure. We investigated the prognostic utility of sST2 for predicting clinical outcomes in hospitalized coronavirus disease 2019 (COVID-19) patients. In a total of 52 hospitalized COVID-19 patients, sST2 levels were measured using the ichroma ST2 assay (Boditech Med Inc., Chuncheon-si, Gang-won-do, Republic of Korea). Clinical outcomes included intensive care unit (ICU) admission, ventilator use, extracorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
2
0
2
Order By: Relevance
“…In autoimmune diseases, sST2 has been shown to be associated with disease activity in conditions such as systemic lupus erythematosus [ 29 ] and rheumatoid arthritis [ 30 ]. In infectious diseases, sST2 levels have been reported to be elevated in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection [ 31 ] and sepsis [ 9 , 32 ]. In cancer, sST2 levels have been linked to tumor progression and metastasis [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In autoimmune diseases, sST2 has been shown to be associated with disease activity in conditions such as systemic lupus erythematosus [ 29 ] and rheumatoid arthritis [ 30 ]. In infectious diseases, sST2 levels have been reported to be elevated in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection [ 31 ] and sepsis [ 9 , 32 ]. In cancer, sST2 levels have been linked to tumor progression and metastasis [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Деякі дослідження довели, що циркулюючі рівні sST2 вищі у пацієнтів з гострим інфарктом міокарда, гострою та хронічною серцевою недостатністю і навіть зі смертністю, а також ці показники корелювали із ремоделюванням серця, зниженням фракції викиду, нейрогормональними порушеннями [1]. Рівень sST2 зростає відповідно до тяжкості перебігу COVID-19, а також асоціюється із госпіталізацією у відділення інтенсивної терапії, використанням апарату штучної вентиляції легень, тромбозом і смертністю від COVID-19 [16]. Згідно з рекомендаціями Фонду Американського коледжу кардіології та Американської кардіологічної асоціації (ACCF/AHA), запропоновано використовувати sST2 як прогностичний біомаркер для оцінки ризику фіброзу міокарда і для прогнозування захворювань серця.…”
Section: Prognostic Value Of Sst2 and Vwf Determination In Blood Seru...unclassified
“…У низці досліджень було запропоновано розглядати sST2 як маркер для визначення важкості перебігу COVID-19 у пацієнтів із супутньою серцево-судинною патологією. Встановлено, що sST2 є не лише важливим маркером серцевої недостатності, його рівень також підвищується в пацієнтів з ГРДС, бронхіальною астмою і сепсисом [1,16]. У пацієнтів з COVID-19 підвищений рівень sST2 був пов'язаний з важчим перебігом і потребою в лікуванні у відділенні інтенсивної терапії, застосуванням штучної вентиляції легень, тромбозом та смертю [16].…”
Section: порівняння показників коагулограми в пацієнтів з аг та Covid-19unclassified
“…Given the global pandemic, there have been a number of studies evaluating the use of biomarkers for disease prognosis among hospitalized patients with COVID-19 [5][6][7][8]. Previous studies have shown that low lymphocyte, platelet counts and albumin levels, and elevated C reactive protein (CRP), white blood cell (WBC) count, blood urea nitrogen, interleukin-6 (IL-6), blood urea nitrogen, creatine kinase, procalcitonin, D-dimer, lactate dehydrogenase, alanine aminotransferase, aspartate aminotransferase and creatinine levels are all associated with poor COVID-19 outcomes [9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%